Braille Teaching Aids Based on the combination of Push Button and Voicing with Voice Chip aP89341 - Mashoedah Mashoedah (LPPM UNY, 2012)
This research was aimed at developing an aid for teaching Braille letters by using Atmega 8535 microcontroller and voice chip aP89341 and the combination of Push Button Switch into the combination of Braille letters. The research method employed was Research and Development with combinations of vowels-consonants and punctuations of Braille letters in Bahasa Indonesia processed into voices by a microcontroller and a voice chip. This aid was validated by five teachers in the Yaketunis School for the Blind to test its feasibility as a teaching aid. The aid was tested on five blind subjects. The performance of the system showed that the aid could produce voicing for 254 combinations of Braille letters consisting of the introduction on the use of the aid, combination of Braille numbers from 0 to 99, combinations of Braille letters from a to z, combinations of Braille vowels and consonants from ba-bi-bu-be-bo to za-zi-zu-ze-zo and their combinations, combinations of Braille punctuations and several additional voicings. The experts' validations were: effectiveness = 81%, user friendliness = 78%, consistency = 78%, media organisation = 80%, and significance = 70%. The percentage of the feasibility test was 77%, categorized as veryfeasible. Keywords: braille teaching aids, push button, voicing, voice chip